A Prospective, Randomized Controlled Trial Design To Evaluate The Effective Role Of Procalcitonin In Adopting Antibiotic Therapy In Sepsis Patients In A Tertiary Care Center - M, Hema.; Rao, V.R. Mohan; R, Anjuka.; E, Vibuja. (Journal of Neonatal Surgery, 2025)
Background: Sepsis is a critical health challenge associated with high morbidity and mortality. Judicious use of antibiotics is highly essential to combat sepsis effectively while mitigating the rise of antimicrobial resistance. Procalcitonin (PCT), a biomarker that elevates during bacterial infections, offers the potential for adopting antibiotic therapy due to its dynamic response to treatment. This study enables to evaluate the efficacy of PCT-guided therapy in optimizing antibiotic use among sepsis patients. Methods: This prospective, randomized controlled trial enrolled 150 patients diagnosed with sepsis based on Sepsis-3 criteria. Participants were randomized into two groups: 1)PCT-Guided Therapy Group: Antibiotic initiation and cessation guided by PCT levels.2)Standard Care Group: Antibiotic management based on clinical assessment . The primary outcome was the duration of antibiotic therapy. Secondary outcomes included clinical cure rate, length of ICU stay, 28-day mortality, and development of antibiotic resistance. Data were analyzed using appropriate statistical tests, with a p-value < 0.05 considered significant. Results: The PCT-guided group showed a significant reduction in the duration of antibiotic therapy(7.2 vs. 10.5 days, p < 0.001) and ICU stay (10.1 ± 3.4 vs. 12.7 ± 4.1 days, p < 0.01). Clinical cure rates (88% vs. 85%, p = 0.52) and 28-day mortality (18.7% vs. 20%, p = 0.79) were comparable between groups. The incidence of antibiotic-resistant infections was lower in the PCT group (7% vs. 15%, p = 0.04). No significant adverse events were reported. Conclusion: PCT-guided therapy effectively reduced antibiotic duration, ICU stay, and antibiotic resistance without compromising clinical outcomes, demonstrating its potential to enhance antimicrobial stewardship in sepsis management. Future studies should refine PCT algorithms and assess long-term effectiveness in diverse settings